2002
DOI: 10.2320/matertrans.43.1197
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of WC-WB-W<SUB>2</SUB>B Composites from B<SUB>4</SUB>C-W-WC Powders and their Mechanical Properties

Abstract: Sintered composites of WC-WB-W 2 B were prepared from B 4 C-W-WC powders using a reactive energization hot-pressing technique that initiated a solid state reaction between B 4 C and W. Below a WC mole fraction of 0.769 in the starting powder, WB and WC were formed according to the reaction B 4 C + 5W + xWC = WB + (1 + x)WC, while WB, W 2 B, and WC were produced above a mole fraction of 0.854. Densely sintered bodies were not obtained for pure WC. Composites of WC-WB-W 2 B obtained at WC mole fractions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…2,4) The powder mixtures were consolidated in a graphite die with an inner diameter of 20 mm and outer diameter of 50 mm at 1600 to 1900 C using a resistance-heated hotpressing system (the Spark-Plasma Sintering Machine; Sumitomo Coal Mining, SPS-2080) at a heating rate of 50 C min À1 , an applied pressure of 50 MPa, and a holding time at the sintering temperature of 20 min. This hot-pressing system enables rapid heating and cooling because an electrically conductive sample and graphite die wound with graphite felt for thermal insulation are heated by passing a current through them directly via water-cooled electrodes that are used for applying pressure simultaneously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4) The powder mixtures were consolidated in a graphite die with an inner diameter of 20 mm and outer diameter of 50 mm at 1600 to 1900 C using a resistance-heated hotpressing system (the Spark-Plasma Sintering Machine; Sumitomo Coal Mining, SPS-2080) at a heating rate of 50 C min À1 , an applied pressure of 50 MPa, and a holding time at the sintering temperature of 20 min. This hot-pressing system enables rapid heating and cooling because an electrically conductive sample and graphite die wound with graphite felt for thermal insulation are heated by passing a current through them directly via water-cooled electrodes that are used for applying pressure simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…Since the Co binder phase lowers the hardness, recent efforts to obtain harder materials have attempted the use of hot pressing to consolidate WC-Co with low amounts of Co 1) and WC with no metallic binder. [2][3][4] In such cases, tungsten hemicarbide (W 2 C) is usually produced during sintering. In addition to these processes, W 2 C is formed in thermally sprayed coatings of WC-Co 5,6) and WC 7) which are used to create wear-resistant hard surfaces on metals.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic binders like Co greatly improve fracture toughness but induces debasement in Young's modulus, hardness and corrosion resistance. We have searched ceramic binders to consolidate WC without debasing these properties, and found that addition of WB-W 2 B [1][2][3] or W 2 C 4) to WC is effective to decrease sintering temperature in hot pressing. However, these additives did not improve fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The sintering procedure and characterization methods for sintered bodies were similar to those described previously. 5,7) The powder mixtures were consolidated at 1600 to 1800 C using a resistance-heated hot pressing system (SPS-2080, the Spark-Plasma Sintering Machine; Sumitomo Coal Mining) at a heating rate of…”
Section: Methodsmentioning
confidence: 99%
“…4WB þ ð1 þ xÞWC ðx 130Þ occurs during sintering. 5) This reactive hot-pressing method was based on the technique developed by Barsoum and Houng,6) who synthesized a dense TiB 2 -TiC composite. W-C-B ceramics with good mechanical properties were obtained at an x value of 80, in which the composition in the reaction equation was 95 mol% WC.…”
Section: Introductionmentioning
confidence: 99%